10. Dosimetric commissioning of PB and MC algorithms for a synchrotron based proton PBS delivery. (December 2018) - Carlino, A.; Kragl, G.; Böhlen, T.T.; Osorio, J.; Grevillot, L.; Vatnitsky, S.; Stock, M.
Abstract : Purpose: In the present work we report the dosimetric commissioning of PB and MC algorithms available in the TPS RayStation for proton PBS delivery installed at the MedAustron particle facility. The work was subdivided into two parts: 1D/2D commissioning consisted of benchmarking both algorithms against measured PDDs, lateral spot profiles in air and measurements in presence of lateral heterogeneities; 3D commissioning consisted of characterization of 3D dose distributions with increasing complexity up to clinical cases. A robotic patient positioning system was used to reduce the air gap between patient and nozzle, therefore special attention was paid to non-isocentric setups especially in presence of Range Shifter (RaShi). Methods: Commissioning was performed for the PB (version 4.1) and the MC (version 4.0) integrated in the RayStation (version 6.1). PDDs were acquired with a Bragg peak chamber (PTW). Spot profiles in air were acquired with a scintillating screen (Lynx, IBA). Measurements of transverse dose profiles in water in presence of lateral heterogeneities were carried out with a micro-diamond (PTW). 3D dose distributions were characterized using a 24 PinPoint chambers block (PTW). Results: Calculated ranges for both algorithms agreed within 0.2 mm with measured ranges. Better agreement of MC (5%) in comparison to PB (10%) for spot sizes (FWHM) in presence of RaShi was obtained. The measurements with micro-diamond showed superior performance of MC in comparison to PB in presence of lateral heterogeneities at larger depths in water (Table 1 ). For complex plans with RaShi computed with PB the deviations are larger compared to MC (Fig. 1). Conclusions: Clinically acceptable results were obtained for open beams with both algorithms. For plans with RaShi and in presence of lateral heterogeneities, MC showed substantially improved performances compared to PB. Therefore, MC is currently established as standard algorithm for treating complex clinical cases at MedAustron.